Integrating Sustainable Development Goals into educational information systems: toward a theoretical model for sustainable school management - Arinal, Veri; Miswanto, Miswanto; Setiawan, Kiki; Rahayu, Agus Tanti (Institute of Advanced Engineering and Science, 2026)
This research addresses the critical challenge of implementing Sustainable Development Goal (SDG) 4,